Hadith #1353 - Sunan al-Nasa'i - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Atab bin Bashayr عتاب بن بشير; ibn Abbas; Ikrama عكرمة; Khsyf bin 'Abdur Rahman al-Jzry خصيف بن عبد الرحمن; Mujahid bin Jabir مجاهد بن جبر (Sunan al-Nasa'i)
A man saw in a dream that it was said to him: “What does your Prophet (ﷺ) command you to do?” He said: “He commanded us to say Tasbih thirty-three times following the prayer, and to say the tahmid thirty-three times, and to say the takbir thirty-four times, and that makes one-hundred.” He said: Say the tasbih twenty-five times and say the tahmid twenty-five times and say the takbir twenty-five times and say the tahlil twenty-five times, and that will make one hundred.” The following
Grade:

Hadith #2754 - Sunan al-Nasa'i - ibn Abbas; Khsyf bin 'Abdur Rahman al-Jzry خصيف بن عبد الرحمن; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Jubayr سعيد بن جبير الأسدي (Sunan al-Nasa'i)
“The Talbiyah of the Messenger of Allah was: “Labbaika Allahumma Labbaik, Labbaika la sharika laka labbaik. Innal-hamda wan-ni’mata laka wal-mulk, la sharika lak (Here I am, O Allah, here I am. Here I am, You have no partner, here I am. Verily all praise and blessings are Yours, and all sovereignty, You have no partner.”
Grade:

Hadith #3080 - Sunan al-Nasa'i - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; ibn Abbas; Khsyf bin 'Abdur Rahman al-Jzry خصيف بن عبد الرحمن; Mujahid bin Jabir مجاهد بن جبر (Sunan al-Nasa'i)
That the Messenger of Allah stoned the Jamarat with pebbles like date sones or fingertips.
Grade:

Hadith #3081 - Sunan al-Nasa'i - al-Fadl bin Musa al-Synany الفضل بن موسى السيناني; al-Husain bin Dhakwan al-Mua'lam الحسين بن ذكوان المعلم المكتب; Ata' bin Abi Rabah عطاء بن أبي رباح; Hilal bin al-'Ala' bin Hilal bin 'Umar هلال بن العلاء بن هلال بن عمر; ibn Abbas; Khsyf bin 'Abdur Rahman al-Jzry خصيف بن عبد الرحمن; Mujahid bin Jabir مجاهد بن جبر; Sa'id bin Jubayr سعيد بن جبير الأسدي; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan al-Nasa'i)
“The Messenger of Allah stoned the Jamarat with pebbles like date sones or fingertips.”
Grade:

Hadith #4147 - Sunan al-Nasa'i - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Amr bin Yahya bin 'Ammara عمرو بن يحيى بن عمارة; Khsyf bin 'Abdur Rahman al-Jzry خصيف بن عبد الرحمن; Mujahid bin Jabir مجاهد بن جبر; Sharayk bin 'Abdullah bin Abi Namr شريك بن عبد الله بن أبي نمر (Sunan al-Nasa'i)
“When the Messenger of Allah distributed the share for his relatives to Banu Hashim and BanuA-Muttalib, I came to himwith ‘Uthman bin ‘Affan and we said: ‘O Messenger of Allah, no one denies the virtue of Banu Hashim because of the relationship between you and them. But how come you have given (a share) to Banu Al-Muttalib and not to us? They and we share the same degree of relationship to you. ‘The Messenger of Allah said: “They did not abandon me during the Jahiliyyah or in Islam.
Grade:

Hadith #3970 - Sunan Abi Dawud - Abdul Wahid bin Ziyad عبد الواحد بن زياد العبدي; ibn Abbas; Khsyf bin 'Abdur Rahman al-Jzry خصيف بن عبد الرحمن; Maqsim bin Bajra مقسم بن بجرة; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
A man got up (for prayer) at night, he read the Qur’an and raised his voice in reading. When the morning came, the Messenger of Allah (ﷺ) said: May Allah have mercy on so-and-so! Last night he reminded me a number of verses which I was about to forget.
Grade: Sahih

Hadith #4054 - Sunan Abi Dawud - ibn Abbas; Ikrama عكرمة; Khsyf bin 'Abdur Rahman al-Jzry خصيف بن عبد الرحمن; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
Abdullah AbuUmar, client of Asma’, daughter of AbuBakr, said: I saw Ibn Umar buying a Syrian garment in the market. When he saw that it had red warp, he returned it. I then came to Asma’ and mentioned it to her. She said: Bring me, slave-girl, the mantle of the Messenger of Allah (ﷺ). She brought out a mantle of a course ornamented cloth, with its collar, sleeves, front, and back were hemmed with brocade.
Grade: Sahih

Hadith #136 - Jami' al-Tirmidhi - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; ibn Abbas; Khsyf bin 'Abdur Rahman al-Jzry خصيف بن عبد الرحمن; Maqsim bin Bajra مقسم بن بجرة; Sharayk bin 'Abdullah شريك بن عبد الله النخعي (Jami' al-Tirmidhi)
the Prophet said about a man who had sexual intercourse with his wife while she is menstruating: “He should give half a Dinar in charity.”
Grade:

Hadith #410 - Jami' al-Tirmidhi - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Atab bin Bashayr عتاب بن بشير; ibn Abbas; Ikrama عكرمة; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Khsyf bin 'Abdur Rahman al-Jzry خصيف بن عبد الرحمن; Mujahid bin Jabir مجاهد بن جبر (Jami' al-Tirmidhi)
“We were with the Prophet (S) on a journey when it started to rain on us, so the Prophet (S) said: ‘Whoever wishes, let him perform Salat in his place.'”
Grade:

Hadith #462 - Jami' al-Tirmidhi - Abdul 'Aziz bin Jurayj عبد العزيز بن جريج; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Khsyf bin 'Abdur Rahman al-Jzry خصيف بن عبد الرحمن; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي (Jami' al-Tirmidhi)
“I asked Aishah about what (recitation) Allah’s Messenger would perform Al-Witr with. She said: ‘In the first he would recite: Glorify the Name of your Lord the Most High, in the second: Say: O you disbelievers!, and in the third: Say: Allah is One” and, Al-Mu’awwidhatain.'”
Grade:

Hadith #622 - Jami' al-Tirmidhi - Abdul Salam bin Harb bin Salm al-Mala'i عبد السلام بن حرب بن سلم النهدي الملائي; Abdullah bin Sa'id al-Ashaj عبد الله بن سعيد بن حصين الكندي - الأشج; Abu 'Ubaidah ibn al-Jarrah; ibn Mas'ud; Khsyf bin 'Abdur Rahman al-Jzry خصيف بن عبد الرحمن; Muhammad bin 'Ubaid bin Muhammad محمد بن عبيد بن محمد بن واقد (Jami' al-Tirmidhi)
the Prophet said: “A Tabi or a Tabi’ah (is due) on thirty cows, and a Musinnah (is due) on every forty.”
Grade:

Hadith #819 - Jami' al-Tirmidhi - Abdul Salam bin Harb bin Salm al-Mala'i عبد السلام بن حرب بن سلم النهدي الملائي; ibn Abbas; Khsyf bin 'Abdur Rahman al-Jzry خصيف بن عبد الرحمن; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Jubayr سعيد بن جبير الأسدي (Jami' al-Tirmidhi)
“Al-Baida the one they lie about regarding the Messenger of Allah. By Allah! The Messenger of Allah did not start the Talbiyah except from near the Masjid, near the tree.”
Grade:

Hadith #3196 - Jami' al-Tirmidhi - Abdul Wahid bin Ziyad عبد الواحد بن زياد العبدي; Khsyf bin 'Abdur Rahman al-Jzry خصيف بن عبد الرحمن; Maqsim bin Bajra مقسم بن بجرة; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Jami' al-Tirmidhi)
Their sides forsake their beds (32:16) – “It was revealed about waiting for Salat which you call Al-‘Atamah.”
Grade:

Hadith #1229 - Sunan Ibn Majah - Abdul 'Aziz bin Jurayj عبد العزيز بن جريج; Khsyf bin 'Abdur Rahman al-Jzry خصيف بن عبد الرحمن; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي (Sunan Ibn Majah)
It was narrated from Ibn ‘Abbas that the Prophet (ﷺ) recited the Opening of the Book (Al-Fatihah) in the funeral prayer.
Grade:

Hadith #1876 - Sunan Ibn Majah - Abdul Salam bin Harb bin Salm al-Mala'i عبد السلام بن حرب بن سلم النهدي الملائي; Abu 'Ubaidah ibn al-Jarrah; ibn Mas'ud; Khsyf bin 'Abdur Rahman al-Jzry خصيف بن عبد الرحمن; Sufyan bin Wky' bin al-Jrah سفيان بن وكيع بن الجراح (Sunan Ibn Majah)
Be moderate in seeking worldly things, for everyone will be facilitated for which he was created.”
Grade:

Hadith #3154 - Sunan Ibn Majah - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; ibn Abbas; Khsyf bin 'Abdur Rahman al-Jzry خصيف بن عبد الرحمن; Mujahid bin Jabir مجاهد بن جبر (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade drinking (directly) from the mouth of a water skin.”
Grade: